2007
DOI: 10.1063/1.2827040
|View full text |Cite
|
Sign up to set email alerts
|

Electron Momentum Spectroscopy and Its Applications to Molecules of Biological Interest

Abstract: Articles you may be interested inKinetic processes in supercooled monosaccharides upon melting: Application of dielectric spectroscopy in the mutarotation studies of D-ribose Dissociation of the ground state vinoxy radical and its photolytic precursor chloroacetaldehyde: Electronic nonadiabaticity and the suppression of the H+ketene channel Theoretical investigation of the eight low-lying electronic states of the cis-and trans-nitric oxide dimers and its isomerization using multiconfigurational second-order pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27] Previous studies have established that EMS is an attractive technique to investigate conformations of organic molecules and small biomolecules. [17][18][19][20][21][28][29][30][31][32][33] It has been demonstrated that the symmetries of the HOMOs with respect to the minimal structures of C s and C 2 on the potential-energy surface (PES) produced by pseudorotation differentiate the conformers of THF. 17 detailed theoretical analysis of the individual valence orbitals of the three important structures, C s , C 2 , and C 1 produced by pseudorotation of THF.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27] Previous studies have established that EMS is an attractive technique to investigate conformations of organic molecules and small biomolecules. [17][18][19][20][21][28][29][30][31][32][33] It has been demonstrated that the symmetries of the HOMOs with respect to the minimal structures of C s and C 2 on the potential-energy surface (PES) produced by pseudorotation differentiate the conformers of THF. 17 detailed theoretical analysis of the individual valence orbitals of the three important structures, C s , C 2 , and C 1 produced by pseudorotation of THF.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, calculations far from trivial are necessary to accurately reveal inner-shell properties and simple models are usually unable to reveal the subtle differences caused by various chemical environment and conformation of biomolecules. For example, tautomers of DNA bases [2,5,7] exhibit only minor differences in energy, but reveal significant configurational changes in the core shell [16,17]. This paper reports recent applications in simulating ionization spectroscopy including synchrotron sourced X-ray spectroscopy and electron momentum spectroscopy (EMS) to study both core and valence structures for biomolecules.Fully optimized geometries are obtained using density functional theory (DFT) B3LYP/aug-cc-pVTZ or B3LYP/6-311G** models incorporated in Gaussian03 [18], followed by vibrational analysis to ensure minimum energy structures.…”
mentioning
confidence: 99%